False-positive dengue serology in a patient of coronavirus disease 2019 (Indian Journal of Case Reports, 2020)
Dengue and coronavirus disease 2019 (COVID-19) both are currently prevalent in India, more so due to the ongoing monsoon season. In such a scenario, it is imperative to distinguish between the two, as both share many similarities in a clinical presentation such as fever and myalgia. Herein, we describe a case of elderly gentleman, aged 68 years, who presented to the emergency department with complaints of dyspnea and chest pain. On evaluation, he had dengue IgM positive with NS1 antigen negative. Later on, he was diagnosed as false positive. The patient was found to be COVID positive on reverse transcription polymerase chain reaction. This case illustrates the importance of differentiating between COVID-19 and dengue.